3-Oxo-N′,2-diphenyl-2,3-dihydro-1H-pyrazole-4-carbohydrazide - Mague, Joel T. (International Union of Crystallography, 2014)
In the title compound, C(16)H(14)N(4)O(2), the pyrazole ring makes a dihedral angle of 10.49 (8)° with its N-bound phenyl group, while it is nearly perpendicular to the other phenyl ring [dihedral angle = 88.47 (5)°]. The molecular conformation is stabilized by intramolecular C—H⋯O and N—H⋯O hydrogen bonds. In the crystal, the packing involves sheets of molecules parallel to (100) linked by N—H⋯O hydrogen bonds. A C—H⋯O interaction is also observed.